Structural functions in music - Berry, Wallace (New York Dover publications, 1987)
A brilliant investigation into musical structure and experience through a systematic exploration of tonality, melody, harmony, texture and rhythm, and their important interpretations. These are illuminated in penetrating analyses of musical works ranging from early madrigals and Gregorian chants through Bach, Beethoven and Brahms to Ravel, Bartók and Berg. Index. Prefaces. Introduction.